Towards Ratiometric Sensing of Amyloid Fibrils In Vitro. Issue 8 (8th January 2015) - Freire, Sonia; Rodríguez‐Prieto, Flor; Ríos Rodríguez, M. Carmen; Penedo, J. Carlos; Al‐Soufi, Wajih; Novo, Mercedes
Abstract: The aggregation of amyloid‐β peptide and its accumulation in the human brain has an important role in the etiology of Alzheimer's disease. Thioflavin T has been widely used as a fluorescent marker for these amyloid aggregates. Nevertheless, its complex photophysical behavior, with strong wavelength dependencies of all its fluorescence properties, requires searching for new fluorescent probes. The use of 2‐(2′‐hydroxyphenyl)imidazo[4, 5‐ b ]pyridine (HPIP), which shows two emission bands and a rich excited‐state behavior due to the existence of excited‐state intramolecular processes of proton transfer and charge transfer, is proposed. These properties result in a high sensitivity of HPIP fluorescence to its microenvironment and cause a large differential fluorescence enhancement of the two bands upon binding to aggregates of the amyloid‐β peptide. Based on this behavior, a very sensitive ratiometric method is established for the detection and quantification of amyloid fibrils, which can be combined with the monitoring of fluorescence anisotropy. The binding selectivity of HPIP is discussed on the basis of the apparent binding equilibrium constants of this probe to amyloid‐β (1–42) fibrils and to the nonfibrillar protein bovine serum albumin. Finally, an exhaustive comparison between HPIP and thioflavin T is presented to discuss the sensitivity and specificity of these probes to amyloid aggregates and the significant advantages of the HPIP dye for quantitative determinations. Abstract : Probing behavior : A sensitive ratiometric method, based on a fluorescent probe undergoing excited‐state intramolecular processes of proton transfer and charge transfer, is proposed for the detection and quantification of amyloid fibrils (see figure).